2016
DOI: 10.1371/journal.pcbi.1004839
|View full text |Cite
|
Sign up to set email alerts
|

A Geometrically-Constrained Mathematical Model of Mammary Gland Ductal Elongation Reveals Novel Cellular Dynamics within the Terminal End Bud

Abstract: Mathematics is often used to model biological systems. In mammary gland development, mathematical modeling has been limited to acinar and branching morphogenesis and breast cancer, without reference to normal duct formation. We present a model of ductal elongation that exploits the geometrically-constrained shape of the terminal end bud (TEB), the growing tip of the duct, and incorporates morphometrics, region-specific proliferation and apoptosis rates. Iterative model refinement and behavior analysis, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…2D). Indeed, as recently reported (Paine et al, 2016), we confirmed that a vast majority of the cap-in-body cell population (69.1 ± 13.1%) was apoptotic, measured by cleaved caspase 3 (cc3) expression and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays (Fig. 2E, Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…2D). Indeed, as recently reported (Paine et al, 2016), we confirmed that a vast majority of the cap-in-body cell population (69.1 ± 13.1%) was apoptotic, measured by cleaved caspase 3 (cc3) expression and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays (Fig. 2E, Fig.…”
Section: Resultssupporting
confidence: 90%
“…2A). Cap cells display expeditious cell cycling, with durations in the range of 16 h (Paine et al, 2016). To test whether cap-in-body cell clusters are a product of cell division, we assessed p63 CreERT2/+ lineage-traced TEBs at early time points, where GFP + cells are labeled more sparsely to ask if labeled clusters were clonal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations